(untitled) (Revista Electrónica Calidad en la Educación Superior, 2025)
This research is on the relevance of educational podcasts from academic specialists’ perspective who have developed them in conjunction with the UNED´s Audiovisual Material Production Program (PPMA) producers. It is a qualitative and bibliographic study that considers the PPMA’s more than 40 years of experience in the production of educational material. The objective was to analyze the perception of the agents involved in the production process of educational podcasts, examining this procedure, its protocol and the approach of an audiovisual pedagogical mediation in the PPMA. Based on results, the importance of educational podcasts in media and information literacy processes is underlined. These results were presented at the VII Alfamed Congress, October 2024, Costa Rica.